ANALISIS PENGARUH EVENT TERHADAP KEPUTUSAN BERKUNJUNG KE KOTA TANGERANG (STUDI KASUS FESTIVAL PEH CUN) - Veronica Suandi; Roozana Maria Ritonga (Cross-border, 2023)
This research uses a type of quantitative research with an explanatory research and sampling techniques applying the nonprobability sampling method using questionnaires. Determination of the number of samples using the slovin formula from the population of the number of visits to Tangerang City for the 2022 period. The data collection technique was obtained through the distribution of questionnaires to 100 respondents who had visited the Peh Cun Festival. The data analysis techniques used by researchers include validity tests, reliability tests, mean descriptive tests, normality tests, heterokedasticity tests, multicollinearity tests, coefficient of determination (R2) tests, multiple linear regression tests, F tests and t tests with the help of the SPSS version 26 program. Based on the results of research conducted with the t test, it shows that each dimension owned by the event variabel (X) has a partial influence on the depennden variabel, namely the decision to visit (Y). Then the result of the F test show that the event variabel (X) has a stimulating influence on the visiting decision variabel (Y). Based on the results of the normality test and heterokedasticity test, it can be seen that the data in this study are normally distributed and heterokedasticity does not occur.